Acute radial artery ischemia following therapeutic steroid injection - Swindells, Mark G; Tehrani, Hamid; Goodwin-Walters, Anna; Sassoon, Elaine M (Annals of plastic surgery, 2007)
Intra-arterial corticosteroid injection at the wrist can have devastating consequences. Anatomic arterial variation of the hand can lead to atypical presentation. A careful history and examination, with appropriate investigations, can lead to an accurate diagnosis in such difficult cases.